2020
DOI: 10.1021/acs.langmuir.0c00443
|View full text |Cite
|
Sign up to set email alerts
|

Structurally Tunable pH-Responsive Luminescent Assemblies from Halogen Bonded Supra-π-amphiphiles

Abstract: Supra-amphiphiles constituted of noncovalent bonds have emerged as attractive systems for fabrication of stimuli-responsive self-assembled nanostructures. A unique supramolecular strategy utilizing halogen (X)-bonding interaction has been demonstrated for constructing emissive supra-π-amphiphiles in water from a hydrophobic pyridyl functionalized naphthalene monoimide (NMI-Py) based X-bond acceptor and hydrophilic iodotetrafluorophenyl functionalized polyethylene glycol (PEG-I) or triethylene glycol (TEG-I) ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 59 publications
1
23
0
Order By: Relevance
“…Solvent‐dependent absorption studies (Figure 4c) revealed ≈10 nm blue‐shift [15] in the absorption maxima (λ max =404 nm) in iPrOH compared to that in CHCl 3 (λ max =414 nm), indicating similar H‐type aggregation of the NMI‐dye on the surface of the 2D crystals. PL studies showed a slight reduction in the emission intensity with emission maxima (λ em ) at ≈520 nm in iPrOH (Figure 4c) compared to the monomeric dye in CHCl 3 owing to the known aggregation caused quenching effect of this dye [15c] . Similar to MC‐P1, no visible changes in the absorption and emission spectra, and platelet size and shape (Figure S13) were noted for a 4‐day aged solution of NMI‐P1, suggesting identical colloidal stability of its 2D crystals.…”
Section: Resultsmentioning
confidence: 99%
“…Solvent‐dependent absorption studies (Figure 4c) revealed ≈10 nm blue‐shift [15] in the absorption maxima (λ max =404 nm) in iPrOH compared to that in CHCl 3 (λ max =414 nm), indicating similar H‐type aggregation of the NMI‐dye on the surface of the 2D crystals. PL studies showed a slight reduction in the emission intensity with emission maxima (λ em ) at ≈520 nm in iPrOH (Figure 4c) compared to the monomeric dye in CHCl 3 owing to the known aggregation caused quenching effect of this dye [15c] . Similar to MC‐P1, no visible changes in the absorption and emission spectra, and platelet size and shape (Figure S13) were noted for a 4‐day aged solution of NMI‐P1, suggesting identical colloidal stability of its 2D crystals.…”
Section: Resultsmentioning
confidence: 99%
“…Water resistant halogen bonds may be the future of biomimetic materials design. Notably, many halogen bond acceptors are nitrogenous bases which confers pH responsiveness to the self‐assembled materials [100–101] . If coupled with suitable donor motifs, they can be explored for finding applicability in sustained and targeted drug delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Needless to say that this applicability can pave the way for future design of self‐assembled biosensors for recognizing various biological processes and responding to different biological analytes [129] . Recent studies have demonstrated halogen bonding to be an extremely powerful tool for surface functionalization in aqueous medium [100–101] . Thus, future studies on surface decoration of macromolecules with functional halogen bond partners, responsive to biological targets will be extremely crucial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, the variation of the XB-acceptor towards a pyridyl functionalized naphthalene monoimide (NMI-Py) with one acceptor moiety per molecule led to fibers upon complexation with PEG-1, whereas TEG-1 resulted in vesicles. 40 …”
Section: Xb In Polymersmentioning
confidence: 99%